2023
DOI: 10.1155/2023/9916294
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexities of Adolescent Bullying: The Interplay between Peer Relationships, Emotion Regulation, and Victimization

Abstract: Bullying is a major social problem that is receiving increased attention in society and research. The overarching goal of the current study was to identify risk and protective factors of bullying examining direct effects between peer relationship, emotion regulation, and bullying involvement. Therefore, a cross-sectional study was conducted with N = 201 students (55.7% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In this perspective, emotional responses associated with bullying victimization adversely affect adolescents' cognitive flexibility [40], and may thus negatively impact their CER [39]. Previous studies have reported a higher use of dysfunctional CER strategies (e.g., catastrophizing, self-blame, blaming others, and rumination) among bullied school students as compared with non-bullied school students [41], emphasizing the possibility that bullying victimization could be related to poor cognitive systems of emotion regulation [42]. Considering that a greater use of dysfunctional CER has been associated with high psychopathological symptoms in adolescents [43,44], CER strategies may be potential mediators of the association between bullying victimization and mental difficulties in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, emotional responses associated with bullying victimization adversely affect adolescents' cognitive flexibility [40], and may thus negatively impact their CER [39]. Previous studies have reported a higher use of dysfunctional CER strategies (e.g., catastrophizing, self-blame, blaming others, and rumination) among bullied school students as compared with non-bullied school students [41], emphasizing the possibility that bullying victimization could be related to poor cognitive systems of emotion regulation [42]. Considering that a greater use of dysfunctional CER has been associated with high psychopathological symptoms in adolescents [43,44], CER strategies may be potential mediators of the association between bullying victimization and mental difficulties in this population.…”
Section: Introductionmentioning
confidence: 99%